Restoration of mitochondrial energy metabolism by electroconvulsive therapy in adolescent and juvenile mice - Du, Ning; Xie, Yu; Geng, Dandan; Li, Jingran; Xu, Heyan; Wang, Yuna; Gou, Jijia; Tan, Xiwen; Xu, Xiaoming; Shi, Lei; Chen, Yujia; Chen, Fengming; et al. (Frontiers in Psychiatry, 2025)
BackgroundAdolescent depression is an increasingly serious public health issue, and traditional treatment methods often have side effects or limited efficacy. Electroconvulsive therapy (ECT), a widely used treatment for severe depression, has recently gained attention for its potential in treating adolescent depression. Previous studies suggest that mitochondrial dysfunction is closely related to the onset of depression. Therefore, investigating the mechanism by which ECT alleviates depressive symptoms through the improvement of mitochondrial energy metabolism is of great significance.MethodsThis study employed the chronic unpredictable mild stress (CUMS) mouse model to assess the effects of ECT on depression-like behaviors through the sucrose preference test, open field test, and tail suspension test. Additionally, mitochondrial energy metabolism markers, including ATP levels, oxygen consumption rate (OCR), lactate, and pyruvate, were measured in both mouse and human plasma to evaluate the effects of ECT on mitochondrial function.ResultsThe results showed that ECT significantly improved depression-like and anxiety-like behaviors in mice, as evidenced by the reversal of abnormal behaviors in the sucrose preference test, open field test, and tail suspension test. Analysis of plasma mitochondrial energy metabolism markers revealed that ECT significantly increased ATP levels, restored OCR, reduced lactate accumulation, and increased pyruvate levels. These findings suggest that ECT alleviates depressive symptoms by restoring mitochondrial energy metabolism and improving brain energy supply.ConclusionThis study systematically explored the potential mechanism by which ECT alleviates adolescent depression through the improvement of mitochondrial energy metabolism. The results indicate that ECT not only effectively alleviates depressive symptoms but also provides new insights and experimental evidence for the treatment of adolescent depression through mitochondrial function restoration. Future research could further investigate how to combine drug treatments to enhance mitochondrial function, improve ECT efficacy, and evaluate the effects of ECT in different depression subtypes, providing guidance for personalized clinical treatment.